Autologous fecal microbiota transplantation for the treatment of inflammatory bowel disease - Basson, Abigail R (Transl Res, 2020)
The term autologous fecal microbiota transplantation (a-FMT) refers herein to the use of one's feces during a healthy state for later use to restore gut microbial communities after perturbations. Generally, heterologous fecal microbiota transplantation (h-FMT), where feces from a ``healthy” donor is transplanted into a person with illness, has been used to treat infectious diseases such as recurrent Clostridioides difficile infection (CDI), with cure rates of up to 90%. In humans, due to limited response to medicines, h-FMT has become a hallmark intervention to treat CDI. Extrapolating the benefits from CDI, h-FMT has been attempted in various diseases, including inflammatory bowel disease (IBD), but clinical response has been variable and less effective (ranging between 24% and 50%). Differences in h-FMT clinical response could be because CDI is caused by a Clostridial infection, whereas IBD is a complex, microbiome-driven immunological inflammatory disorder that presents predominantly within the gut wall of genetically-susceptible hosts. FMT response variability could also be due to differences in microbiome composition between donors, recipients, and within individuals, which vary with diet, and environments, across regions. While donor selection has emerged as a key factor in FMT success, the use of heterologous donor stool still places the recipient at risk of exposure to infectious/pathogenic microorganisms. As an implementable solution, herein we review the available literature on a-FMT, and list some considerations on the benefits of a-FMT for IBD.